TRATAMENTO ENDODÔNTICO E CIRURGICO DE CISTO PERIAPICAL EXTENSO COM REMOÇÃO DE FÍSTULA EXTRA-ORAL - RELATO DE CASO - JOSLIN, Tatiane Camargo Wenceslau; da SILVA, Vanessa Schüssler; KLÜPPEL, Leandro Eduardo; ZEDEBSKI, Rosario Arruda Moura; SARTORI, Rafael (DENS, 2011)